ST-elevation myocardial infarction in a young patient with Duchenne's muscular dystrophy: a case report. Issue 5 (16th May 2022) - Mitropoulou, Panagiota; Hobson, Alexander; Morton, Geraint; Anantharam, Brijesh
Abstract: Background: Duchenne's muscular dystrophy (DMD) is an X-linked muscular disease which is caused by the absence of dystrophin. This results in the death of muscle cells and cardiomyocytes and consequent substitution by fat and fibrous tissue. The clinical translation of this is muscle weakness and cardiomyopathy. We report on the case of a young patient with dilated cardiomyopathy on a background of DMD who developed ST-elevation myocardial infarction (STEMI). Case summary: A 19-year-old male patient with DMD, known dilated cardiomyopathy, and no risk factors for ischaemic heart disease presented with central crushing chest pain. His electrocardiogram revealed anterior ST elevation. His angiogram revealed distally occluded left anterior descending and second diagonal branch with no evidence of underlying coronary artery disease. He was treated with balloon angioplasty. An echocardiogram raised the suspicion of a left ventricular thrombus, and the mechanism of STEMI was felt to be embolism from the left ventricular thrombus on a background of dilated cardiomyopathy in the context of DMD. The patient was treated with anticoagulants (warfarin). On a repeat echocardiogram a few months later, the thrombus had resolved. At 3 years of follow-up, the patient did not present any more embolic events. Discussion: To our knowledge, this is the first case of STEMI secondary to thrombotic coronary occlusion that has been described in a patient with DMD. This case highlights an unusual complication of DMD. Based on this case, we discuss the dilemmas in the management and follow-up of this complex patient population.